Evidence in Support of Potential Applications of Lipid Peroxidation Products in Cancer Treatment - Erejuwa, Omotayo O.; Sulaiman, Siti A.; Wahab, Mohd S. Ab (Hindawi Publishing Corporation, 2013)
Cancer cells generate reactive oxygen species (ROS) resulting frommitochondrial dysfunction, stimulation of oncogenes, abnormal metabolism, and aggravated inflammatory activities. Available evidence also suggests that cancer cells depend on intrinsic ROS level for proliferation and survival. Both physiological and pathophysiological roles have been ascribed to ROS which cause lipid peroxidation. In spite of their injurious effects, the ROS and the resulting lipid peroxidation products could be beneficial in cancer treatment. This reviewpresents research findings suggesting that ROS and the resulting lipid peroxidation products could be utilized to inhibit cancer growth or induce cancer cell death. It also underscores the potential of lipid peroxidation products to potentiate the antitumor effect of other anticancer agents.The review also highlights evidence demonstrating other potential applications of lipid peroxidation products in cancer treatment. These include the prospect of lipid peroxidation products as a diagnostic tool to predict the chances of cancer recurrence, to monitor treatment progress or how well cancer patients respond to therapy. Further and detailed research is required on how best to successfully, effectively, and selectively target cancer cells in humans using lipid peroxidation products.This may prove to be an important strategy to complement current treatment regimens for cancer patients.